Developing Arabic Educational Games in ‘Arabiyah Lil Athfal Entrepreneurship Course Using Project-Based Learning - Maziyyatul Muslimah (Maharaat: Jurnal Pendidikan Bahasa Arab, 2022)
Arabic educational games proven to have the advantages of making learning more entertaining also enhancing students' interest and excitement for learning Arabic. In light of these benefits, studies suggest that Arabic language teachers should receive training in the design, planning, implementation, and evaluation of educational games in order to enrich learning and teaching experiences, activate learner's role, and benefit from educational games to achieve targeted direct knowledges. However, there is a paucity of research on teaching prospective Arabic teachers to build Arabic instructional games, particularly in the entrepreneurial context. Using qualitative methods, this study aims to indicate the project-based learning approach utilized to create Arabic instructional games as part of Arabiyah lil Athfal Entrepreneurship course in State Islamic University (IAIN) of Kediri, East Java, Indonesia. It is found that project-based learning in Arabiyah Lil Athfal's class satisfied several defined criteria: centrality, driving question, constructive investigations, autonomy, and realism. The project was demonstrated to be a substantial component of the course and worthy of being regarded core.